Integrating Point-of-Care Ultrasonography Into the Osteopathic Medical School Curriculum - Russ, Brian A.; Evans, Danika; Morrad, Daniel; Champney, Codee; Woodworth, Ashley M.; Thaut, Lane; Thiessen, Molly (Journal of Osteopathic Medicine (Online), 2017)
Point-of-care ultrasonography has been shown to have pervasive clinical and educational utility in medicine. The need to provide medical students with training in point-of-care ultrasonography has been recognized by an increasing number of osteopathic and allopathic medical schools. A 4-year integrated ultrasonography curriculum was implemented at Rocky Vista University College of Osteopathic Medicine in 2015. A review of the curriculum design, content, educational methods, and student feedback are described. Barriers to curriculum implementation and lessons learned, unique to integrating point-of-care ultrasonography into the osteopathic curriculum, are also discussed.